Supply of Potable Water in Kuttanad and Regulation of Water Salinity - KUMAR, N.KRANTHI; mounika, p (The journal of contemporary issues in business and government, 2020)
The Thanneermukkam bund has various problems, including water pollution and the spread of submerged aquatic plants like sea weeds, which were erected to ease the salty concerns faced by Kuttanad's farmers. Thanneermukkam Bund's principal objective is to lessen the salinity level of Vembanad Lake during the summer season, which is the period of the check (TMB). The problem can be fixed easily if the following guidelines are followed. A controller transports Muvattupuzha River water to the Kuttanad area where it is diluted and maintained at 2ppt salinity; in times of severe shortage, water is collected in the pazhnilam and sent to Lake Girding through a pump. Kuttanad's colourful operating techniques and controller design are also thrown about as a way to execute the concept. A plan to use Kuttanad's volume and saltiness of the natural water system is under consideration.Kuttanad, salinity, and add-ons are some of the terms in this section.